Effect of Haemophilus influenzae Type b Vaccination on Nasopharyngeal Carriage Rate in Children, Tehran, 2019 - Tabatabaei, Sedigheh Rafiei (Biomed Res Int, 2021)
BACKGROUND: Haemophilus influenzae (H. influenzae) strains, which commonly reside as commensals within the human pharynx and can remain as an asymptomatic carrier, but become invasive leading to pneumonia, septic arthritis, or meningitis. The Pentavac (pentavalent vaccine, manufactured by India, SII (DTwP-HepB-Hib)) was introduced to the Iranian National Immunization Plan in November 2014. The aim of this study is to investigate H. influenzae type b (Hib) carrier rate among children under 6 years old in Tehran. METHODS: This cross-sectional study was performed on 902 children including vaccinated/unvaccinated in the age of 6 months to 6 years, in Tehran. Sampling was performed from July 2019 to September 2019. Nasopharyngeal samples were taken from children by sterile swab. The PCR method was used to extract DNA. Then, all H. influenzae isolates were initially confirmed by molecular tests. BexA was used to distinguish typeable H. influenzae strains from nontypeable Haemophilus influenzae (NTHi). RESULTS: A total of 902 children were enrolled in the study: 452 were female (51%). H. influenzae carriage rate was 267 (29%), of that 150 samples (16.6%) were typeable. The nasopharyngeal Hib carrier rate in the children was 2.6% (24/902). 262 cases did not receive Hib vaccine. Analysis in nonnursery's children aged 4 to 6 (unvaccinated) years showed that the lower educational level of father, mother, and family number correlated with increased odds of colonization of children with Hib. CONCLUSION: Our findings showed a significant decrease (60%) in the overall Hib nasopharyngeal carriage in healthy children under six years after 5 years after the start of Hib vaccination.